Development and apllication of an ambulatory esophageal manometry system - Bremner, Ross Macrae (My University, 2016)
The aim of this project was to develop an automated system capable of monitoring intraesophageal pressures for prolonged periods of time, and to evaluate the clinical relevance of this system. Stationary esophageal manometry is, at present, the cornerstone of assessing esophageal motor function. it's shortcomings, related to the brevity of the test and the unphysiologic environment in which it is performed, have limited our understanding of esophageal motility abnormalities. The goal of this study was to overcome these shortcomings. The thesis first describes the development of the hardware and software required to continuously monitor, and then analyze, pressures and pH from the esophagus in the ambulatory individual over a 24-hour period. Validation of the automated analysis and establishment of normal values are then described. The system was then used to evaluate patients with functional esophageal disorders in the esophageal laboratory at the University of Southern California (USC), Los Angeles. Many patients with gastroesophageal reflux disease were found to have a profound motility defect of the esophageal body as evidenced by an inability to improve propulsive function during meals. This defect was not apparent on stationary manometry and has important implications for anti-reflux surgery. The increased sensitivity of ambulatory manometry in detecting poor motor function is now being used to tailor surgery in those requiring operative repair at USC. Patients with primary esophageal motor disorders such as diffuse esophageal spasm, achalasia, nutcracker esophagus and hypertensive lower esophageal sphincter were found to have many overlapping features whick inspired a new classlfication based on discussed. The added advantage of combining a PH probe with the pressure manometer is the ability to dectect clearance mechanisms in normal subjects and patients with gastroesophageal reflux disease. The ability to record pharyngeal pressures using this system demonstrated the importance of pharyngeal induced peristalsis in clearing the esophagus of refluxed acid. Clearance mechanisms were found to be related to the state of consciousness and provided an explanation for the severe mucosal complications seen in patients with excessive nocturnal reflux. The clearance mechanisms of patients with Barrett's esophagus were shown to be compromised because of an alteration in the sensitivity of the columnar mucosal feedback mechanisms resulting in delayed and phlegmatic pharyngeal swallowing after the onset of a reflux episode. This thesis describes the new insights afforded by ambulatory manometry and the benefits of having this intormation prior to instituting therapy in patients with esophageal disorders. The developed system can be performed with little added discomfort to the patient undergoing pH monitoring. It is hoped that the ease of performing the test and the added insight provided by the study will encourage the use of ambulatory manometry as the gold-standard for evaluating esophageal motor disorders.
A dissertation Submitted to the Faculty of Medicine University of the Witwatersrand, Johannesburg For the Degree of Doctor of Philosophy (Medicine). Johannesburg and Los Angeles, 1997